International Relations Club Scrapbook (1950-1951) - (:unkn) unknown (My University, 1952)
The girls that participated in the International Relations Club went to a Conference that took place at the Citadel Military College in Charleston, South Carolina on March 1st, 2nd, and 3rd. There was a meeting called by the President of the Citadel Patrick J. Bohem who introduced the conference. The minutes from this conference meeting are attached along with some of the photos that were taken during this time. There is also an I.R.C Newsletter attached along with some information about the surrounding area where the conference takes place.
International Relations Club (I.R.C). "1950-1951," 1952. 1 electronic record. 1 pdf document. 9 scans.
Keywords: International Relations Club; Scrapbook